2006
DOI: 10.1056/nejmsa044464
|View full text |Cite
|
Sign up to set email alerts
|

Who Is at Greatest Risk for Receiving Poor-Quality Health Care?

Abstract: The differences among sociodemographic subgroups in the observed quality of health care are small in comparison with the gap for each subgroup between observed and desirable quality of health care. Quality-improvement programs that focus solely on reducing disparities among sociodemographic subgroups may miss larger opportunities to improve care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
277
12
4

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 446 publications
(310 citation statements)
references
References 23 publications
17
277
12
4
Order By: Relevance
“…The lower rate of recommended care among older adults might be related to the higher number of indicators for which older adults became eligible or to lower attention to preventive care. Our findings of lower preventive care in the elderly are similar to those of a previous US study, 2 but need to be confirmed by further research. The higher level of quality of care for CVRFs compared to preventive care might be explained by the ease of ordering laboratory tests or prescribing new medications compared to counseling on lifestyle modifications or cancer screening.…”
Section: -11supporting
confidence: 87%
See 1 more Smart Citation
“…The lower rate of recommended care among older adults might be related to the higher number of indicators for which older adults became eligible or to lower attention to preventive care. Our findings of lower preventive care in the elderly are similar to those of a previous US study, 2 but need to be confirmed by further research. The higher level of quality of care for CVRFs compared to preventive care might be explained by the ease of ordering laboratory tests or prescribing new medications compared to counseling on lifestyle modifications or cancer screening.…”
Section: -11supporting
confidence: 87%
“…We selected 37 quality indicators from RAND's QA Tools 1,2 concerning preventive care and the care of CVRFs. This system was previously developed in the US to evaluate the quality of care delivered to adults.…”
Section: Quality Indicatorsmentioning
confidence: 99%
“…In the U.S., Asch et al showed that ethnicity moderately determines overall quality of care: In terms of preventive care, hispanics had statistically significant higher scores than other ethnic group. 2 Higher overall scores of quality of care were found for young patients (<31 years) than the elderly (>64 years), women than men, Blacks and Hispanics than Caucasians and those with a high income (>$50,000) than those with incomes of less than $15,000. 2 Most other US studies focused on specific indicators or conditions making a comparison with our results difficult and found moderate variation of quality of care among different ethnic groups.…”
Section: Discussionmentioning
confidence: 90%
“…2 Higher overall scores of quality of care were found for young patients (<31 years) than the elderly (>64 years), women than men, Blacks and Hispanics than Caucasians and those with a high income (>$50,000) than those with incomes of less than $15,000. 2 Most other US studies focused on specific indicators or conditions making a comparison with our results difficult and found moderate variation of quality of care among different ethnic groups. 10,11 Gray et al showed that in the UK, non-Whites were significantly less likely to meet the national treatment targets for hemoglobin A1c, blood pressure, and cholesterol.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation